Factor Analysis to Explore the Indicators of Quality Assurance Mechanism on Higher Educational Institutions in Pakistan - Huma Shahid,; Zaira Wahab ,; Syed Afrozuddin Ahmed, (Journal of Basic & Applied Sciences, 2016)
The study aims to gauge the effectiveness of Quality Assurance Mechanism (QAM) and its impact on quality of education in Higher Education Institutions in Pakistan. In this study, a comprehensive survey was conducted, through a well-structured questionnaire, to collect essential data from the respondents. A total of 300 teachers of 5 private and 5 public sector universities were participated in the study. The Cronbach’s alpha reliability value is found to be almost 0.80 for all construct of the instrument in this study. An independent t- test was carried out to reveal the significant difference among private and public sector universities in terms of quality of education. The p-value (significance value) of this test in each construct indicates that there is significant difference among private and public sector universities regarding quality assurance practices. Furthermore, the multivariate statistical tool “Exploratory Factor Analysis (EFA)” was used to explore the underlying pattern of the public and private sector universities data. Finally, four factors emerged in the data whose eigen value are greater than one. Factors emerges in public sector universities data represents teacher’s satisfaction and combination of budget allocation and funding while factors that emerges on private sector universities are the combination of globalization, ranking and adequate funding.